TANTANGAN DESA WISATA DALAM PEMBERDAYAAN MASYARAKAT STUDI KASUS DESA WISATA TANJUNG KALURAHAN DONOHARJO KECAMATAN NGAGLIK KABUPATEN SLEMAN - Iriannita Salim; Ardiyati (Halu Oleo University, 2025)
Tourism Village in Tanjung Tourism Village. This research uses qualitative methods and involves research subjects who are involved in the management of tourist villages, tourist village managers, and other parties who contribute. The results showed that the development of Tanjung Tourism Village was successfully developed well, this can be seen from the attractions presented, accommodation, affordability, infrastructure, community involvement and adequate environmental sustainability in the development process resulting in community empowerment that contributes to: (1) human capacity development through training to improve the quality of human resources and tourism services. (2) Business capacity development through the formation of MSME groups to increase production capacity and market access. (3) development of environmental capacity through the preservation of the natural and social environment, as well as the application of the principles of “nature” and renewable energy. (4) Institutional Capacity Development through the effectiveness of social organisations to support human, business, and environmental development.